Pre-Alpine contrasting tectono-metamorphic evolutions within the Southern Steep Belt, Central Alps - Roda, M.; Zucali, M.; Li, Zheng-Xiang; Spalla, M.; Yao, Weihua (Elsevier BV, 2018)
© 2018 Elsevier B.V. In the Southern Steep Belt, Italian Central Alps, relicts of the pre-Alpine continental crust are preserved. Between Valtellina and Val Camonica, a poly-metamorphic rock association occurs, which belongs to the Austroalpine units and includes two classically subdivided units: the Languard-Campo nappe (LCN) and the Tonale Series (TS). The outcropping rocks are low to medium grade muscovite, biotite and minor staurolite-bearing gneisses and micaschists, which include interlayered garnet- and biotite-bearing amphibolites, marbles, quartzites and pegmatites, as well as sillimanite-bearing gneisses and micaschists. Permian intrusives (granitoids, diorites and minor gabbros) emplaced in the metamorphic rocks. We performed a detailed structural, petrological and geochronological analysis focusing on the two main lithotypes, namely, staurolite-bearing micaschists and sillimanite-bearing paragneisses, to reconstruct the Variscan and Permian-Triassic history of this crustal section. The reconstruction of the tectono-metamorphic evolution allows for the distinction between two different tectono-metamorphic units during the early pre-Alpine evolution (D1) and predates the Permian intrusives, which comprise rocks from both TS and LCN. In the staurolite-bearing micaschists, D1 developed under amphibolite facies conditions (P = 0.7–1.1 GPa, T = 580–660 °C), while in the sillimanite-bearing paragneisses formed under granulite facies conditions (P = 0.6–1.0 GPa, T > 780 °C). The two tectono-metamorphic units coupled together during the second pre-Alpine stage (D2) under granulite-amphibolite facies conditions at a lower pressure (P = 0.4–0.6 GPa, T = 620–750 °C) forming a single tectono-metamorphic unit (Languard-Tonale Tectono-Metamorphic Unit), which comprised the previously distinguished LCN and TS. Geochronological analyses on zircon rims indicate ages ranging between 250 and 275 Ma for D2, contemporaneous with the emplacement of Permian intrusives. This event developed under a high thermal state, which is compatible with an extensional tectonic setting that occurred during the exhumation of the Languard-Tonale Tectono-Metamorphic Unit. The extensional regime is interpreted as being responsible for the thinning of the Adriatic continental lithosphere during the Permian, which may be related to an early rifting phase of Pangea.